Epidemiological Characteristics and Clinical Features of Patients Infected With the COVID-19 Virus in Nanchang, Jiangxi, China - Hong, Jian-Ming; Hu, Long-Hua; Zhong, Qiao-Shi; Zhu, Long-Chuan; Hang, Ya-Ping; Fang, Xue-Yao; Sun, Hua-Bao; Huang, Zhi-Hua; Xu, Jianping; Chen, Yan-Hui (Frontiers in Medicine, 2020)
Objectives: The 2019 novel coronavirus disease (COVID-19) pandemic is the biggest public health crises in the 21st century. While most patients infected with the COVID-19 virus have no to moderate symptoms, there is currently limited clinical information about these patients. Methods: In this study, we retrospectively investigated 41 patients infected with the COVID-19 virus in Nanchang, Jiangxi province, China, from February 4 to March 2, 2020. Nanchang is about 260 km southeast of Wuhan, the initial epicenter of the COVID-19 pandemic. We retrieved information on patient demographics, physical examination results, epidemiology, clinical manifestations, underlying conditions, laboratory analyses, radiological images, and treatment outcomes. Results: Most patients (70.7%) had a history of close contact with patients with confirmed COVID-19, and 16 patients (39.0%) showed a high degree of family clustering. All 41 patients had no to moderate symptoms. The median age was 39.9 years and common symptoms of illness were fever (69.2%), cough (65.4%), and fatigue (19.2%). The dominant patient group was middle-aged women, with hypertension (14.6%) and chronic liver disease (12.2%) as the most frequent underlying conditions. All patients recovered, with the mean time of viral nucleic acid clearance at 10.6 days. Chest CT scans presented ground-glass opacities in 53.7% of patients while 26.8% had normal CT images. Laboratory results showed that lymphocyte counts, lymphocyte percentages, ESR, CRP, IgG, Fib, and cytokines were correlated to patients' conditions. Approximately 60–90% of patients had abnormally high levels of cytokines IL-4, IL-6, IL-10, and/or TNF-α. Conclusions: Our results showed variable clinical and laboratory presentations among this group of patients infected with the COVID-19 virus. Though all 41 patients recovered, our results suggest that cytokine levels and other biochemical indicators should be monitored for patients infected with the COVID-19 virus showing no to moderate symptoms to ensure quick access for critical medical attention, if needed.